CONFORMITIES TO LAW OF FORMING LAYER FOR POLYDISPERSE PELLET CHARGE ON SINTER BELT - Pazyuk, Mikhail; Mnykh, Anton; Ovchіnnіkova, Irina; Kuris, Yurii (Scientific Journal "Metallurgy", 2021)
Motion of pellet charge on the loading tray on a sinter belt is accompanied not only by the change of its grain-size composition, but by segregation processes, id est. by the redistribution of charge of different size particles for the most part friable material. The result of this process is formation of local discontinuity with pre-dominance of content for particles of certain factions. The traditional method for analysis of work for loading tray on the basis of factious classification does not allow to educe and analyze appearing heterogeneity in the most part friable material. It results in errors at the calculation for action of the system of the automated control by sintering process and ignoring of notational of the use of segregation of particles of friable material for optimization of technological process. The use of balance method enables to specify and spread understanding of mechanism of processes which take place during motion of pellet charge in relation to the loading tray, and also to form theoretical pre-conditions for the choice of the rational modes of operations of agglomeration separation of sintering plant. It is set that at monotonous increase of angle of slope for loading tray the segregation phenomena increase in a pellet charge, and after achievement of the defined value – go down, id est. have extreme character. Mentioned features of forming of layer for polydisperse material in the conditions of inconstancy of mechanical properties of its separate factions it is possible to take into account at the use of balance of grain-size composition of charge, loaded on a sinter belt, and charge, being on it, when conditional middle diameters of particles of their components must be equal. On the basis of the set conformities to law of forming of friable of structure of layer the method of authentication of grain-size compositions of pellet charge mixture is in theory reasonable in every its horizon taking into account a segregation during loading.